Martial arts and psychosocial development in primary education: A systematic review of social-emotional learning (SEL) - Herdiansyah; Subarjah, Herman; Mahendra, Agus; Alif, Muhammad Nur; Baharuddin, Syaipul Hari (UIR Press, 2025)
Background: Social-emotional learning (SEL) competencies are critical for children’s academic engagement and psychosocial well-being. Martial arts, which integrate structured practice, ethical instruction, and social interaction, are increasingly implemented in primary education; however, their effects on SEL outcomes in primary-school-aged children have not yet been systematically synthesized. Objectives: This systematic review aims to examine the effects of martial arts interventions on emotion regulation, executive function, and empathy among primary school children aged 6–12 years. Methods: This systematic review followed PRISMA 2020 guidelines. Literature searches were conducted in Scopus, PubMed, SAGE Journals, SpringerLink, and Emerald Insight up to August 2025. Eligibility criteria were established using the PICOS framework. Nine empirical studies published between 2015 and 2025 were included. Study selection, data extraction, and risk-of-bias assessment were independently performed by two reviewers using Covidence, with RoB 2 applied to randomized studies and the JBI checklist to non-randomized designs. Owing to methodological heterogeneity, findings were synthesized narratively. Findings/Results: School-based and curriculum-integrated martial arts interventions were associated with improvements in children’s emotion regulation, executive functioning, and empathy. Positive outcomes were most evident in programs incorporating structured practice, reflective or mindfulness-based activities, cooperative learning, and autonomy-supportive pedagogy. Effects varied according to program duration, instructional fidelity, and pedagogical design, with limited or inconsistent findings reported for short-term or extracurricular interventions lacking explicit socioemotional components. Conclusion: Martial arts can be an effective pedagogical approach for enhancing SEL-related psychosocial competencies in primary education when delivered through structured, value-based programs. Future studies should prioritize standardized curricula, robust experimental designs, and longitudinal follow-up to determine the sustainability of intervention effects.